Pemanfaatan Daging Kodok Sawah (Fejervarya cancrivora) sebagai Inovasi Produk Kuliner Sate Tradisional - Ito Garcia Febrianto; Sri Yulianto Fajar Pradapa; Artin Bayu Mukti (LPPM Institut Pendidikan Nusantara Global, 2026)
As the demand for sustainable alternative protein grows, rice paddy frog (Fejervarya cancrivora) meat emerges as a promising option. However, its potential remains hindered by cultural stigma and an unfamiliar natural aroma. This study addresses this challenge by transforming frog meat into a familiar local favorite—satay—and evaluating how consumers accept it. Using a quantitative descriptive approach, we gathered insights from 30 selected respondents through hedonic and sensory intensity evaluations. The results are highly encouraging, showing an overall consumer acceptance rate of 80.00%. Texture and taste led the preferences (83.33% each), followed closely by color (80.00%) and aroma (66.66%). Notably, these acceptance scores surpass previous studies that processed amphibian meat without using a familiar culinary format. We found that combining an acid treatment, distinctive satay spices, and precise grilling successfully masked the undesirable aromas and boosted overall appeal. These findings confirm that adapting unconventional ingredients into well-loved traditional dishes is an effective strategy for local food diversification.